PRINCIPLES OF ASSESSING THE QUALITY OF PROFESSIONAL TRAINING IN COLLEGES OF ECONOMICS (Innovative professional education, 2024)
The subsection is devoted to the problem of assessing the quality of vocational training at colleges as an important prerequisite for achieving sustainable development of society. The quality of vocational training at colleges was also considered as a tool for effective management of the competitiveness of the country’s personnel potential. To create and effectively use the system of assessment in an educational institution, the criteria, principles and functions of evaluating the quality of vocational training were clearly defined.
Keywords: assessment; economic colleges; future professional junior bachelors; vocational higher education